Implementation of Online Learning Whatsapp Group Students' Islamic Education Courses Muhammadiyah High School 2 Medan - Siti Halimah; Hasan Matsum; Muhammad Junaidi (Budapest International Research and Critics University, 2022)
This study aims to determine: (1) learning planning carried out by Islamic Education teachers using whatsapp groups, (2) implementation of the learning process carried out by Islamic Education teachers using whatsapp groups, and (3) learning evaluations carried out by Islamic Education teachers. The research was conducted at SMA Muhammadiyah 2 Medan. This type of research is qualitative research. Primary data sources are informants consisting of: principals, teachers and students, then secondary data sources are written documents in the form of school profiles, syllabus, learning implementation plans, photos of school activities, learning outcomes documents. The data collection instrument used was interviews, observation and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The research findings show: (1) learning planning begins with developing a learning implementation plan at the beginning of the semester by considering core competencies, basic competencies, school vision and mission as well as student needs and using a format that has been determined by the school, (2) the implementation of Islamic Education learning with the whatsapp group application is carried out as follows: minutes before learning begins, the teacher reminds students to take online learning, the teacher greets students and takes attendance online, the teacher provides the material to be studied in the form of word reading texts, powerpoints and learning videos, the teacher explain the material online so that students can understand the material through voice notes, conduct questions and answers if there are students who do not understand the learning material with the aim that students can better understand the material presented, give assignments to students to collect according to the teacher's directions, and jointly conclude the teaching materials that have been studied, (3) the evaluation of learning is carried out with the following activity stages: daily tests, independent assignment portfolios, mid-semester examinations and end-semester examinations.